Unique technique of surgery in an unusual variety of Scimitar syndrome: A Case Report - Theisen Daniel; Loeff Markus; Januszewska Katarzyna; Nuebel Julia; Malec Edward; Dalla-Pozza Robert (Journal of Cardiothoracic Surgery, 2010)
Abstract Scimitar syndrome is a rare congenital anomaly characterized by total or partial anomalous pulmonary venous drainage of the right lung to the inferior vena cava. We present a seven year old girl with a systolic murmur who was diagnosed as having a Scimitar syndrome with unusual drainage of the right pulmonary veins. The unique technique of surgery in this patient was appropriate to the unusual, previously not described anatomy.